Most Florida dealers dodge destructive Hurricane Ian; Auto plants, dealerships in the Carolinas close ahead of impact - Staff Reports (Automotive News, 2022)
Florida dealership associations described retailers as relatively unscathed after Hurricane Ian soaked and whipped the state last week, while auto plants and dealerships in the Carolinas closed in anticipation of being the storm's next target. Ian made landfall northwest of Fort Myers on Wednesday afternoon as a Category 4 storm with sustained winds of 145 mph. The storm weakened to a tropical storm as it churned across Florida but regained hurricane strength after reaching the Atlantic Ocean on Thursday.